(untitled) (Journal of Bio-Science, 2015)
Context: Water productivity is considered as an important indicator of Agriculture productivity because of the scarcity of freshwater. More yield or output against same or less amount of water has become the global interest. Objectives: This study measures the productivity of water on the floodplain land in terms of Boro rice cultivation for two floodplain beels in Rajshahi Bangladesh. Materials & Methods: For this study, the production and market price data were collected by direct observation based on 30 samples in the year 2006-07. Results: This study found gross water productivity of rice yield as 0.47 kg m-3 in beel Mail and 0.43 kg m-3 in beel Chandpur. In monetary value, water productivity per cubic meter irrigation water were TK 5.65, TK 3.42 and TK 2.64 based on gross return, net return considering cash costs and net return considering full costs in beel Mail. In beel Chandpur these values were TK 5.19 m-3, TK 2.87 m-3 and TK 2.14 m-3, respectively. The usage of average irrigated water in the boro rice farms were estimated 10730.05 m-3 and 11236 m-3 with an average production of yield 4992.95 kg and 4783.20 kg in beel Mail and beel Chandpur. Statistical result shows that keeping irrigation water constant, a 1% increase of boro rice yield will increase water productivity at 0.916% in beel Mail and 0.972% in beel Chandpur. The water productivity in beel Mail was 4.65% higher than beel Chandpur due to the intervention of community based fish culture management. Conclusion: The findings of this study will help to govern and improve production by proper utilizing floodplain lands. DOI: http://dx.doi.org/10.3329/jbs.v21i0.22526 J. bio-sci. 21: 123-136, 2013